2014
DOI: 10.3109/10715762.2014.892937
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide: A central player in physical plasma-induced oxidative stress in human blood cells

Abstract: Plasma medicine is an interdisciplinary field and recent clinical studies showed benefits of topical plasma application to chronic wounds. Whereas most investigations have focused on plasma-skin cell interaction, immune cells are omnipresent in most tissues as well. They not only elicit specific immune responses but also regulate inflammation, which is central in healing and regeneration. Plasma generates short-lived radicals and species in the gas phase. Mechanisms of plasma-cell interactions are not fully un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 51 publications
9
166
2
Order By: Relevance
“…Nonthermal atmospheric plasma (NAP) has been used in the clinical setting to accelerate wound healing [69] . Some changes exerted by NAP were abolished by catalase and the cells' responses to NAP treatment are similar to incubating in H 2 O 2 in a similar concentration [69,70] , as exemplified by the plasma-induced profound extracellular trap formation (NET), which can be inhibited by the presence of catalase. However, adding an equivalent concentration of H 2 O 2 cannot induce NET [71] .…”
Section: Hydrogen Peroxide: Implications For Chronic Wound Treatmentmentioning
confidence: 83%
“…Nonthermal atmospheric plasma (NAP) has been used in the clinical setting to accelerate wound healing [69] . Some changes exerted by NAP were abolished by catalase and the cells' responses to NAP treatment are similar to incubating in H 2 O 2 in a similar concentration [69,70] , as exemplified by the plasma-induced profound extracellular trap formation (NET), which can be inhibited by the presence of catalase. However, adding an equivalent concentration of H 2 O 2 cannot induce NET [71] .…”
Section: Hydrogen Peroxide: Implications For Chronic Wound Treatmentmentioning
confidence: 83%
“…Many types have been identified in plasma-treated liquids in the past years [72]. For the kINPen plasma jet, this includes for example nitrite, nitrate, hydrogen peroxide, superoxide, hydroxyl radical, peroxynitrite, and singlet oxygen [72][73][74]. Plasma gas phase analysis suggests the presence of many others [75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…The approach enabled a quick and reproducible treatment of cells in a 96 well plate and allowed an easy correlation with chemical assays. In vitro/ex vivo findings in different model systems of Bekeschus, 38 Schmidt, 39 and Wende et al 21 further indicated, that a separate treatment of liquids provokes the same biological effect as a direct treatment at least for the kinpen. The same effect has been observed for the plasma jet studied in this work (see Fig.…”
Section: A Motivation Of Treatment Approachmentioning
confidence: 99%